2001
DOI: 10.1002/micr.21709
|View full text |Cite
|
Sign up to set email alerts
|

Non‐vital, prosthetic, and virtual reality models of microsurgical training

Abstract: Many microsurgical training models exist. These can be broadly classified into living and non-living. The latter type can be further sub-classified into non-vital, prosthetic, and virtual reality models. We review each model within these sub-groups with reference to the ideal properties of a training model. The most important attribute of any model is that the skills acquired from it must translate efficiently into microsurgical skill in the clinical situation. We believe that non-vital and prosthetic models a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 32 publications
1
59
0
Order By: Relevance
“…[32][33][34] Review literature on nonliving models showed these are good alternatives and especially useful for initial acquisition and maintenance of microsurgical skills. 35 However, in our opinion, none of the models are validated enough to use as assessment tools.…”
Section: Nonliving Modelsmentioning
confidence: 99%
“…[32][33][34] Review literature on nonliving models showed these are good alternatives and especially useful for initial acquisition and maintenance of microsurgical skills. 35 However, in our opinion, none of the models are validated enough to use as assessment tools.…”
Section: Nonliving Modelsmentioning
confidence: 99%
“…9,11,12 However, living animal models are still needed and justified to simulate the clinical situation, once the participants have reached a high level of tissue control and security in performing vascular anastomoses. 2,13,14 We follow a stepwise training program, 15 starting with nonliving models where participants gain experiences in the use of optical aids, microsurgical instruments and techniques, and tissue manipulation, which reduces the number of required animals substantially.…”
Section: Discussionmentioning
confidence: 99%
“…9 The consequence is a growing interest by resi- dents and qualified surgeons in basic microsurgical training courses. On the other hand, only a few institutions with the requisite capabilities (e.g., necessary equipment, facilities for animal keeping, experienced tutors) offer these courses.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo animal model is ideal for pre-clinical training, where every facet of microsurgery techniques can be exercised with higher complexity, and the end result of the anastomoses can be observed directly. However, it is a complex model for a novice, and the excess use of live animals for surgical training also raised ethical, economical, and logistic conflicts [3][4][5][6][7]. Many non-animal organic and synthetic models are adopted by microsurgical training centers as their first line training methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Many non-animal organic and synthetic models are adopted by microsurgical training centers as their first line training methodology. These models, unlike the in vivo animal models, can be tailored to facilitate targeted exercises, thus trainees can build their technical skills ethically, cost effectively, and systematically [4,5,7]. Among them, latex based models are the most common and has been used for microsurgical training for more than 3 decades [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%